The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

High‐resolution stable isotope profiles from shells of the land snail Placostylus reveal contrasting patterns between snails originating from New Zealand and New Caledonia - Mathieu Quenu; Emily J. Judd; Mary Morgan‐richards; Steven A. Trewick; Katherine Holt; Jonathan Tyler; Andrew M. Lorrey (Journal of Quaternary Science, 2023)
The stable oxygen (δ 18 O shell ) and carbon (δ 13 C shell ) isotope ratios retrieved from the carbonate shell of terrestrial gastropods can be used as an environmental proxy and are thought to reflect dietary composition and ambient climatic conditions (e.g. precipitation amount, humidity, temperature). Here, we generate high‐resolution isotopic profiles of nine modern land snails of the genus Placostylus , collected from two locations in New Caledonia and one location in New Zealand. We found that snails from New Zealand had, on average, higher δ 18 O shell values than their counterparts in New Caledonia, which surprisingly runs counter to the expected relationship based on the isotopic composition of rainwater between these two regions. Specimens from New Caledonia exhibit ephemeral decreases in their δ 18 O shell values, which could be linked to extreme precipitation events in this region, while snails from New Zealand have less variation in their δ 18 O shell values. Snails from New Zealand had, on average, slightly higher δ 13 C shell than their counterparts in New Caledonia, but a large difference in carbon isotopes was sometimes observed between snails collected at the same location. Most snails exhibit a temporal trend in their δ 13 C shell values, indicating potential shifts in diet through to maturity.

Genotypic detection of barriers to rat dispersal: Rattus rattus behind a peninsula predator-proof fence - Shogo Yarita; Mary Morgan-Richards; Steven A. Trewick (Biological Invasions, 2023)
Clear delimitation of management units is essential for effective management of invasive species. Analysis of population genetic structure of target species can improve identification and interpretation of natural and artificial barriers to dispersal. In Aotearoa New Zealand where the introduced ship rat ( Rattus rattus ) is a major threat to native biodiversity, effective suppression of pest numbers requires removal and limitation of reinvasion from outside the managed population. We contrasted population genetic structure in rat populations over a wide scale without known barriers, with structure over a fine scale with potential barriers to dispersal. MtDNA D-loop sequences and microsatellite genotypes resolved little genetic structure in southern North Island population samples of ship rat 100 km apart. In contrast, samples from major islands differed significantly for both mtDNA and nuclear markers. We also compared ship rats collected within a small peninsula reserve bounded by sea, suburbs and, more recently, a predator fence with rats in the surrounding forest. Here, mtDNA did not differ but genotypes from 14 nuclear loci were sufficient to distinguish the fenced population. This suggests that natural (sea) and artificial barriers (town, fence) are effectively limiting gene flow among ship rat populations over the short distance (~ 500 m) between the peninsula reserve and surrounding forest. The effectiveness of the fence alone is not clear given it is a recent feature and no historical samples exist; resampling population genetic diversity over time will improve understanding. Nonetheless, the current genetic isolation of the fenced rat population suggests that rat eradication is a sensible management option given that reinvasion appears to be limited and could probably be managed with a biosecurity programme.

Global warming leads to habitat loss and genetic erosion of alpine biodiversity - Fabio Leonardo Meza‐Joya; Mary Morgan‐Richards; Emily M. Koot; Steven A. Trewick (Journal of Biogeography, 2023)
Aim Species living on steep environmental gradients are expected to be especially sensitive to global climate change, but little is known about the factors influencing their responses to contemporary warming. Here, we investigate the influence of climate on the biogeography of three alpine species with overlapping ranges. Location Te Waipounamu (South Island) Aotearoa–New Zealand. Taxon Endemic alpine adapted Catantopinae grasshoppers. Methods We used niche modelling to estimate and project the potential niche of three focal species under past and future climate scenarios. Vulnerability assessments were performed using niche factor analyses. Demographic trends and phylogeographic structure were investigated using samples from 15 mountain tops to generate mitochondrial DNA haplotype networks and population genetic statistics. Results Niche models and genetic data suggest suitable habitat for all three alpine species was more widespread and contiguous in the past than today. Demographic analyses indicate in situ survival rather than post‐Pleistocene colonisation of current habitat. Population structuring and genetic divergence suggest that mountain uplift during the Pliocene and environmental barriers during Pleistocene glacial and interglacial stages shaped contemporary population structure of each species. Although geographically overlapping, niche analyses suggest these alpine species are not ecologically identical, each showing distinct responses to environmental change, but all will lose intraspecific diversity through population extinction. Main Conclusions Climatic, biological and geophysical factors controlled population structuring of three cold‐adapted species during the Pleistocene with a legacy of spatially separate intraspecific lineages. Ecological niche models for each species emphasise distinct combinations of environmental proxies, but all are expected to experience severe habitat reduction during climate warming. Increased global temperatures drive available habitat to higher elevation resulting in population contractions, range shifts, habitat fragmentation, local extinctions and genetic impoverishment. Despite alpine species not being ecologically identical, we predict all mountain biota will lose significant genetic diversity due to global warming.

Abundance and distribution of antennal sensilla on males and females of three sympatric species of alpine grasshopper (Orthoptera: Acrididae: Catantopinae) in Aotearoa New Zealand - Mari Nakano; Mary Morgan-Richards; Andrea Clavijo-McCormick; Steven Trewick (Zoomorphology, 2023)
Brachaspis nivalis , Sigaus australis and Paprides nitidus are grasshopper species endemic to Aotearoa, New Zealand where they are sympatric in several regions of South Island. On mountains of Kā Tiritiri o te Moana (Southern Alps), B. nivalis is more abundant on scree/rock habitat, whereas S. australis and P. nitidus are prevalent in alpine tussock and herbfields. It is expected, therefore, that these species have different sensory needs that are likely to be apparent in the type, abundance, and distribution of chemo-sensilla on their antennae. It is also likely that natural selection has resulted in sexual differences in sensilla. To test these hypotheses, abundance and distribution of the chemo-sensilla on the dorsal and ventral surfaces of their antennae were characterized in adult males and females of the three species. Five types of chemo-sensilla were identified on the distal portion of their antenna: chaetica, basiconica, trichoidea, coeloconica, and cavity. All species had significantly more chemo-sensilla on the ventral than the dorsal surface of antennae and a similar distribution pattern of chemo-sensilla. Despite having relatively short antenna, B. nivalis had the largest number of olfactory sensilla, but the fewest chaetica of the three species studied. A plausible explanation is that B. nivalis is abundant on less vegetated habitats compared to the other species, and therefore may rely more on olfaction (distance) than gustatory (contact) reception for finding food. No significant differences were observed between the sexes of B. nivalis and P. nitidus , however, S. australis males had significantly more basiconica sensilla than females.